On the interaction between economic growth and business cycles - Ivan Mendieta-Mu\~noz (University of Kent, School of Economics, 2014)
The present paper studies the interaction between short-run fluctuations and economic growth by presenting empirical evidence of the impact of business cycle fluctuations on the rate of growth consistent with a constant unemployment rate in 13 Latin American and 18 OECD countries during the period 1981-2011. The results of both parametric (OLS and a panel estimator that allows for parameter heterogeneity and cross section dependence) and non-parametric (a penalized regression spline estimator) econometric techniques show that this measure of potential output experiences positive (negative) changes in periods of high (low) growth in the majority of countries, and, hence, that business cycles fluctuations have statistically significant effects on potential output. However, in contrast to the sample of OECD countries, less than half of the sample of Latin American countries experience statistically significant changes of this measure of potential output in periods of low growth.
Keywords: E32; O40; O51; O54; 330; growth and cycles; potential rate of growth; rate of growth consistent with a constant unemployment rate